Juridical Analysis of Default Lawsuits in the Implementation of Peace Agreement Letters Due to Alleged Medical Negligence (Case Study of Decision Number 232/pdt. G/2025 PN Medan) - Trie Tirta Nadya Marbun; July Esther; Besty Habeahan (PALAR | PAKUAN LAW REVIEW, 2026)
This research is motivated by a medical dispute due to alleged negligence (malpractice) that has been settled out of court, but the hospital did not implement the contents of the agreement, thus creating legal uncertainty for the patient. The research problem is focused on the validity of the medical dispute settlement agreement and the judge's legal considerations in deciding the default case in Decision Number 232/Pdt.G/2025/PN Medan, with the aim of analyzing the legal status of the settlement deed and legal protection for the injured party. The research method used is normative legal research with a case and statutory approach. The results of the study indicate that the settlement agreement between the patient and the hospital is valid and binding based on Articles 1320 and 1338 of the Civil Code, which changes the legal relationship into a purely contractual relationship. In his decision, the judge stated that the Defendant was in default because he violated the obligation to pay compensation and medical costs that had been agreed upon, so he was sentenced to pay material compensation of Rp266,000,000. It is recommended for the parties that each peace agreement be confirmed through a court decision (Van Dading) or a notarial deed to guarantee stronger executorial powers, and for the hospital to be highly committed to implementing the agreement in order to protect the patient's rights and the institution's reputation. Key Word : Wanprestasi, Peace Agreement, Medical Dispute, Judge's Consideration